Method for evaluating aging resistance of end sealing silicone rubber material of composite insulator

CN122709320APending Publication Date: 2026-09-08CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610843177.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-09-08

AI Technical Summary

Technical Problem

(1)老化条件与实际工况关联性不强:多数加速老化试验采用单一应力或简单复合应力,难以真实模拟端部密封区域的多因素(湿度、温度、盐及酸的腐蚀反应等)耦合作用,导致实验室评价结果与现场服役寿命之间的对应关系较差

Benefits of technology

[0018] Therefore, this invention proposes a complete index testing scheme: by comparing the differences in various performance indicators such as surface morphology detection, Fourier transform infrared spectroscopy detection, mechanical property detection and water permeability detection before and after aging, researchers and manufacturers can quickly screen out high-quality sealing silicone rubber formulations that are more resistant to acid, salt and humid heat, effectively preventing interface breakdown or core rod breakage accidents caused by end seal failure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122709320A_ABST
    Figure CN122709320A_ABST
Patent Text Reader

Abstract

The application discloses a kind of composite insulator end sealing silicon rubber material's ageing resistance performance evaluation method, comprising: silicon rubber sample piece is completely immersed in prepared soaking solution, after being sealed with cover, it is placed in 50 DEG C constant-temperature box and is placed for 30 days, and obtains sample piece after ageing;Surface morphology detection, fourier infrared spectrum detection, mechanical property detection and water permeability detection are carried out to sample piece after ageing and unaged original sample piece respectively, compare each detection result, and obtain the comparison result of each index;According to the comparison result of each index, the ageing resistance performance of silicon rubber material is determined.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power transmission and transformation equipment material testing technology, and more specifically, to a method for evaluating the aging resistance of composite insulator end-sealing silicone rubber material. Background Technology

[0002] Currently, there are few methods for evaluating the aging resistance of end-sealing materials for composite insulators, and most of them involve accelerated aging tests on the entire composite insulator before evaluating related performance, without truly focusing on the aging resistance of the sealing material itself. Existing research and industrial practice mainly employ the following technical approaches: (1) Artificial accelerated aging test method: The composite insulator is subjected to accelerated aging treatment by simulating single or combined environmental stresses (such as ultraviolet irradiation, damp heat aging, salt spray corrosion, temperature cycling, ozone aging, etc.). After the test, the effectiveness of the end seal of the composite insulator is determined by dye penetration, tensile peel test and other tests.

[0003] (2) Chemical structure and thermal performance analysis techniques: Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and other methods are used to analyze the changes in microscopic indicators such as chemical functional groups, crosslinking density and thermal stability of sealing materials during the aging process, so as to infer their aging mechanism and aging resistance.

[0004] Currently, evaluations of silicone rubber materials for composite insulators primarily focus on shed materials, while a comprehensive evaluation system for the aging resistance of end-sealing silicone rubber materials is still lacking. Existing evaluation methods have the following shortcomings: (1) The aging conditions are not strongly correlated with the actual working conditions: Most accelerated aging tests use single stress or simple composite stress, which makes it difficult to truly simulate the coupling effect of multiple factors (humidity, temperature, salt and acid corrosion reaction, etc.) in the end sealing area, resulting in a poor correspondence between laboratory evaluation results and field service life.

[0005] (2) Single evaluation index: Existing methods often only focus on one aspect of the material's intrinsic properties or interface properties, lacking a comprehensive characterization system for the multi-dimensional deterioration law of "material-interface-function" during the aging process of sealing materials, making it difficult to fully reflect the aging resistance of sealing materials.

[0006] Therefore, there is an urgent need to develop an evaluation method that can more realistically simulate the service environment of composite insulator ends, comprehensively evaluate the aging resistance of the sealing material body and interface, and has good engineering operability, so as to fill the gap in the existing technology. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides a method for evaluating the aging resistance of silicone rubber materials used for sealing the ends of composite insulators.

[0008] According to one aspect of the present invention, a method for evaluating the aging resistance of a composite insulator end-sealing silicone rubber material is provided, comprising: The silicone rubber sample was completely immersed in the prepared soaking solution, sealed, and placed in a constant temperature chamber at a preset temperature for a preset number of days to obtain the aged sample. One or more tests, including surface morphology detection, Fourier transform infrared spectroscopy detection, mechanical property detection, and water permeability detection, were performed on aged samples and unaged original samples. The results of each test were compared to obtain the comparative results of each index. Based on the comparison results of various indicators, the aging resistance of silicone rubber materials was determined.

[0009] Optionally, the soaking solution is composed of deionized water as solvent, and sodium chloride, sulfuric acid and nitric acid are added; wherein the mass fraction of sodium chloride is 0.1 wt%, and the concentrations of sulfuric acid and nitric acid are both 2 mol / L.

[0010] Optionally, the silicone rubber sample is a circular sample with a thickness of 2 mm and a diameter of 8 cm.

[0011] Optionally, surface morphology inspection includes: Observe the surface micromorphology of the aged sample and the original sample, and test the surface roughness; If the aged sample shows a significant increase in filler particles, increased pore density, or surface roughness exceeding 1.6 times the original sample, then the silicone rubber material is deemed to have poor aging resistance.

[0012] Optionally, Fourier transform infrared spectroscopy detection includes: Comparing the aged sample with the original sample at a wavenumber of 790 cm⁻¹ -1 Characteristic peak value of Si-(CH3)2 group at the location; If the characteristic peak value of the aged sample drops to less than 70% of the original characteristic peak value, the silicone rubber material is judged to have poor aging resistance.

[0013] Optionally, mechanical property testing includes: The tensile strength, tear strength, and elongation at break of the aged sample and the original sample were tested respectively. If the tensile strength, tear strength, and elongation at break of the aged sample all decrease to below 80% of the corresponding data of the original sample, then the silicone rubber material is judged to have poor aging resistance.

[0014] Optionally, permeability testing includes: The aged sample and the original sample were sealed in glass cups containing deionized water. The glass cups were inverted and kept under conditions where the external relative humidity was less than 1% for a preset number of days. The rate of change in the mass of the water passing through the sample was measured. If the rate of change in the mass of water passing through the aged sample increases to more than 1.3 times that of the original sample, then the silicone rubber material is judged to have poor aging resistance.

[0015] Optionally, the rate of change in quality v The calculation expression is: Where t is the preset number of days; the mass of water passing through the silicone rubber test piece The calculation expression is: In the formula, It is the total mass of the glass and the sealed device for the test piece after water has seeped through. This is the initial total mass of the device.

[0016] Optionally, the aging resistance of the silicone rubber material is determined based on the comparison results of various indicators, including: When at least two test results in the comparison show deterioration, the aging resistance of the silicone rubber material is deemed unqualified.

[0017] Optionally, the preset temperature is 50°C.

[0018] Therefore, this invention proposes a complete index testing scheme: by comparing the differences in various performance indicators such as surface morphology detection, Fourier transform infrared spectroscopy detection, mechanical property detection and water permeability detection before and after aging, researchers and manufacturers can quickly screen out high-quality sealing silicone rubber formulations that are more resistant to acid, salt and humid heat, effectively preventing interface breakdown or core rod breakage accidents caused by end seal failure. Attached Figure Description

[0019] Exemplary embodiments of the present invention can be more fully understood by referring to the following figures: Figure 1 This is a flowchart illustrating an exemplary embodiment of the present invention regarding a method for evaluating the aging resistance of a composite insulator end-sealing silicone rubber material. Figure 2 This is a schematic diagram of a device for measuring the rate of change of water through a sample, provided in an exemplary embodiment of the present invention. Detailed Implementation

[0020] Hereinafter, exemplary embodiments according to the present invention will be described in detail with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments of the present invention. It should be understood that the present invention is not limited to the exemplary embodiments described herein.

[0021] It should be noted that, unless otherwise specifically stated, the relative arrangement, numerical expressions, and values ​​of the components and steps described in these embodiments do not limit the scope of the invention.

[0022] Exemplary methods Figure 1 This is a schematic flowchart illustrating a method for evaluating the aging resistance of a composite insulator end-sealing silicone rubber material, provided in an exemplary embodiment of the present invention. Figure 1 As shown, the method 100 for evaluating the aging resistance of the silicone rubber end-sealing material of composite insulators includes the following steps: Step 101: Immerse the silicone rubber sample completely in the prepared soaking solution, seal it, and place it in a preset stable constant temperature chamber for a preset number of days to obtain the aged sample. Step 102: Perform one or more tests on the aged sample and the unaged original sample, including surface morphology detection, Fourier transform infrared spectroscopy detection, mechanical property detection and water permeability detection, and compare the results of each test to obtain the comparison results of each index. Step 103: Determine the aging resistance of silicone rubber material based on the comparison results of various indicators.

[0023] Specifically, this invention proposes a reasonable testing and evaluation method for the aging resistance of silicone rubber materials used for sealing the ends of composite insulators, consisting of two parts: damp heat accelerated aging test and performance testing and evaluation.

[0024] The process and principle of the damp heat accelerated aging test are as follows: (1) Aging environment: The aging test was carried out by immersion test of the sample, and the solution temperature was set to 50℃. The reason is that 50℃ is the common temperature of the end fittings when the composite insulator is running normally, while immersion in a solution at a temperature higher than normal is used to simulate a humid and hot environment and test the resistance of the end sealing silicone rubber material to humid and hot aging.

[0025] (2) Preparation of soaking solution: The soaking solution mainly consists of deionized water (solvent), sodium chloride, sulfuric acid, and nitric acid. Sodium chloride is used because the coastal environment is affected by sea breezes, and the air in this area has a relatively high salt content. Sulfuric acid and nitric acid are used because the composite insulator has a large electric field strength at its end fittings during operation, and nitrogen and sulfur dioxide in the air may react to generate nitric acid and sulfuric acid under high electric field strength. The presence of sodium chloride, sulfuric acid, and nitric acid will all have a deteriorating effect on the end sealing silicone rubber material, so these components need to be added to the preparation of the soaking solution. The required concentration of sodium chloride in the soaking solution is 0.1wt%, and the required concentration of sulfuric acid and nitric acid is 2mol / L. (3) Aging test: Prepare circular samples with a thickness of 2 mm and a diameter of 8 cm. Immerse the samples completely in the prepared soaking solution, seal them, and place them in a constant temperature chamber at 50°C for 30 days (or other numbers of days, depending on the specific circumstances). The sample size and the device for measuring the rate of change of water permeable through the sample should be compatible. If the size is too large or too small, it will affect the detection effect of water permeability and mechanical properties. Therefore, the size should be compatible with the measuring device and adjusted accordingly.

[0026] After accelerated aging, the aged and unaged samples were subjected to performance tests, including surface morphology observation, Fourier transform infrared spectroscopy, mechanical property testing, and water permeability testing. The detailed content and principles of each test item are as follows: (1) Surface morphology detection: including observation of surface micromorphology and surface roughness detection. If the aged sample has obvious increase in filler particles and pore density, as well as increase in surface roughness (for example, when it increases to more than 1.6 times the original), it indicates that the aged sample has significant silicone rubber degradation and internal filler precipitation, indicating that the material has poor aging resistance.

[0027] (2) Fourier transform infrared spectroscopy detection: Focus on the Si-(CH3)2 group at wavenumber 790cm-1. This group represents the side chain methyl group of silicone rubber. If the characteristic peak of this group decreases significantly after aging (for example, it decreases to less than 70% of the characteristic peak of the original sample), it indicates that the side chain methyl is consumed too much, and the hydrophobicity of the silicone rubber sealing material and its resistance to the penetration of water molecules into the material may be weakened.

[0028] (3) Mechanical property testing: The tensile strength, tear strength and elongation at break of the sample are mainly tested. If all three mechanical properties of the sample decrease significantly after aging (decreased to less than 80% of the corresponding data of the original sample), it indicates that the defects of the material have developed into the interior during aging, indicating that the aging resistance of the silicone rubber sealing material is poor. If the mechanical properties of the end-sealing silicone rubber material decrease rapidly during aging, it will cause the end seal to detach and open, allowing external moisture to penetrate into the interior of the composite insulator.

[0029] (4) Permeability test: Design as follows Figure 2 The device shown is used to measure the rate of change in water mass passing through the sample, and is used to examine the rate of water transmission through the sample before and after aging.

[0030] The specific design method involves filling a 6cm diameter glass beaker with deionized water, placing an 8cm diameter circular sample on the beaker's rim, and sealing the interface between the sample and the beaker with sealing wax. After sealing, the apparatus is inverted. A desiccant is used to maintain the relative humidity of the external environment below 1%. The water pressure on both sides of the sample causes water to permeate through it, continuing for 30 days. During the experiment, the mass of water permeating through the silicone rubber sample is indirectly measured by measuring the total mass change of the sealed apparatus consisting of the glass beaker and the sample. The calculation formula is as follows: in It is the total mass of the glass and the sealed device for the test piece after water has seeped through. This is the initial total mass of the device. Expressed as the rate of change of mass... The rate of water permeability is characterized by the following formula: The permeability of the samples before and after aging was tested and compared. If the rate of change of water mass permeating the sample increased significantly (for example, when it increased to more than 1.3 times that of the original sample), it indicates that the silicone rubber has poor aging resistance.

[0031] In a specific embodiment of the present invention, the following is an example of evaluating the aging resistance of the silicone rubber material used for sealing the ends of a certain type of composite insulator: (1) Preparation of test samples: Prepare samples according to the silicone rubber material formula for the end sealing of this type of composite insulator, and cut out multiple circular samples with a thickness of 2mm and a diameter of 8cm; (2) Accelerated aging test: The samples were subjected to a multi-factor damp heat accelerated aging test. The soaking solution was prepared by mixing deionized water, nitric acid, sulfuric acid and sodium chloride. The concentration of sodium chloride in the soaking solution was required to be 0.1 wt%, and the concentration of sulfuric acid and nitric acid was required to be 2 mol / L. The samples prepared in the previous step were completely immersed in the prepared soaking solution, sealed and placed in a constant temperature chamber at 50°C for 30 days. Another set of several samples with the same formula and size specifications were prepared and not aged, and kept as a control group for later use. (3) Sample performance testing: Take out the sample that has completed the wet heat accelerated aging test in the previous step, clean the residual soaking liquid on the sample surface with deionized water, and let it air dry naturally. Then, perform performance testing on the aged sample and the unaged sample respectively. The specific test items include surface morphology testing, Fourier transform infrared spectroscopy testing, mechanical property testing, and water permeability testing; (3.1) Surface morphology inspection: The surface micromorphology of the sample was observed using a scanning electron microscope to check for changes in filler particle and pore density. The surface roughness of the sample was measured using a roughness tester. (3.2) Fourier transform infrared spectroscopy detection: Fourier transform infrared spectroscopy detection was performed on the sample, focusing on the characteristic peak of the Si-(CH3)2 group with a wavenumber of 790cm-1, and comparing the differences in characteristic peak values ​​between aged and unaged samples.

[0032] (3.3) Mechanical property testing: The tensile properties, tear properties and elongation at break of the unaged and aged samples were tested respectively, and the differences in mechanical properties between the two were compared.

[0033] (3.4) Water permeability test: Based on aged and unaged samples, a device for measuring the rate of change of water permeation through the sample was designed and placed upside down. A desiccant was used to maintain the relative humidity of the external environment below 1%. The water pressure on both sides of the sample caused water to permeate through the sample for 30 days. During the experiment, the mass Δm of water permeating through the silicone rubber sample and the rate of change of water permeation through the sample were indirectly measured by measuring the total mass change of the sealed device consisting of the glass cup and the sample.

[0034] (4) Performance comparison: Based on the results of various performance tests, the aging resistance characteristics of the silicone rubber material for sealing the ends of the composite insulator were evaluated.

[0035] Based on the technical solution of this invention, the method for evaluating the aging resistance of the composite insulator end-sealing silicone rubber material described in this invention has the following expected beneficial effects: (1) Improved the correlation between the experimental environment and actual operating conditions. This invention solves the problem of limited aging conditions in existing technologies by accurately simulating the aging environment.

[0036] ① Scientific environmental parameters: The aging test sets the solution temperature to 50℃, which directly corresponds to the common temperature of the end fittings when the composite insulator is running normally, ensuring the authenticity of thermal stress.

[0037] ② Highly targeted chemical composition: This invention not only adds sodium chloride to the immersion solution to simulate the coastal salt spray environment, but also adds small amounts of sulfuric acid and nitric acid to simulate the strong acidic substances generated by the air reaction triggered by the end fittings under high field strength. This multi-factor (humidity, temperature, salt, acid) coupled immersion test can more realistically reproduce the deterioration process of sealing materials under complex service environments than traditional single stress aging.

[0038] (2) A comprehensive evaluation system with multiple dimensions of "materials-chemistry-function" was constructed. To address the problem that existing technologies use single evaluation indicators that are insufficient to comprehensively reflect material properties, this invention proposes a complete indicator testing scheme: ① Combining macroscopic mechanics with microscopic morphology: By detecting changes in tensile strength, tear strength and elongation at break, the degree of development of internal defects in the material is assessed; at the same time, scanning electron microscopy is used to observe the precipitation of surface fillers and the condition of pores, and a roughness meter is used to detect the surface condition, thus realizing performance evaluation from macroscopic to microscopic.

[0039] ②In-depth analysis of chemical mechanisms: This invention focuses on the characteristic peaks of relevant functional groups in Fourier transform infrared spectroscopy. The degree of loss of these functional groups can explain the weakening of the material's hydrophobicity and resistance to water molecule penetration at the molecular level, providing scientific evidence for the aging mechanism.

[0040] (3) A quantitative evaluation method for sealing function was introduced. To address the lack of a dedicated evaluation method for end-sealing structures in existing technologies, this invention designs a specialized permeability testing device. Focusing on the core function of end-sealing materials—moisture barrier—this invention designs a device for measuring the rate of change in water mass permeating a sample. This method can directly guide the reliability design of composite insulator end-sealing structures and has extremely high reference value for practical engineering.

[0041] (4) It has good engineering operability and promotion value. This invention clarifies the sample preparation specifications, accelerated aging cycle, and specific steps for various tests, providing a clear operational process that facilitates widespread application in the power equipment manufacturing and testing industry. By comparing the performance differences before and after aging, researchers and manufacturers can quickly screen for high-quality sealing silicone rubber formulations that are more resistant to acids, salts, and damp heat, effectively preventing interface breakdown or core rod breakage accidents caused by end seal failure.

[0042] The above description has been given for purposes of illustration and description. Furthermore, this description is not intended to limit the embodiments of the invention to the forms disclosed herein. Although numerous exemplary aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, alterations, additions, and sub-combinations thereof.

Claims

1. A method for evaluating the aging resistance of silicone rubber material used for sealing the ends of composite insulators, characterized in that, include: The silicone rubber sample was completely immersed in the prepared soaking solution, sealed, and placed in a constant temperature chamber at a preset temperature for a preset number of days to obtain the aged sample. The aged sample and the unaged original sample were subjected to one or more tests, including surface morphology detection, Fourier transform infrared spectroscopy detection, mechanical property detection and water permeability detection. The results of each test were compared to obtain the comparison results of each index. Based on the comparison results of various indicators, the aging resistance of the silicone rubber material was determined.

2. The method according to claim 1, characterized in that, The soaking solution is composed of deionized water as solvent, and sodium chloride, sulfuric acid and nitric acid are added; wherein the mass fraction of sodium chloride is 0.1 wt%, and the concentration of sulfuric acid and nitric acid is 2 mol / L.

3. The method according to claim 1, characterized in that, The silicone rubber sample is a circular sample with a thickness of 2 mm and a diameter of 8 cm.

4. The method according to claim 1, characterized in that, The surface morphology detection includes: The surface micromorphology of the aged sample and the original sample were observed, and the surface roughness was detected. If the aged sample shows a significant increase in filler particles, pore density, or surface roughness exceeding 1.6 times the original sample, then the silicone rubber material is deemed to have poor aging resistance.

5. The method according to claim 1, characterized in that, The Fourier transform infrared spectroscopy detection includes: Comparing the aged sample with the original sample at a wavenumber of 790 cm⁻¹ -1 Characteristic peak value of Si-(CH3)2 group at the location; If the characteristic peak value of the aged sample drops to below 70% of the characteristic peak value of the original sample, then the silicone rubber material is determined to have poor aging resistance.

6. The method according to claim 1, characterized in that, The mechanical property testing includes: The tensile strength, tear strength, and elongation at break of the aged sample and the original sample were tested respectively. If the tensile strength, tear strength and elongation at break of the aged sample all decrease to below 80% of the corresponding data of the original sample, then the silicone rubber material is judged to have poor aging resistance.

7. The method according to claim 1, characterized in that, The water permeability test includes: The aged sample and the original sample were sealed in the mouth of a glass containing deionized water. The glass was inverted and kept under the condition that the external relative humidity was less than 1% for a preset number of days. The rate of change in the mass of the water passing through the sample was measured. If the rate of change in the mass of water passing through the aged sample increases to more than 1.3 times that of the original sample, then the silicone rubber material is deemed to have poor aging resistance.

8. The method according to claim 7, characterized in that, The rate of change of mass v The calculation expression is: Where t is the preset number of days; the mass of water passing through the silicone rubber test piece The calculation expression is: In the formula, It is the total mass of the glass and the sealed device for the test piece after water has seeped through. This is the initial total mass of the device.

9. The method according to any one of claims 1 to 8, characterized in that, Based on the comparison results of various indicators, the aging resistance of the silicone rubber material was determined, including: When at least two of the test results in the comparison show deterioration, the silicone rubber material is deemed to have unqualified aging resistance.

10. The method according to claim 1, characterized in that, The preset temperature is 50℃.